Perangkat Lunak Kriptografi Metode Gost - Indra Harahap, Ahmad (Jurnal Nasional Teknologi Komputer, 2022)
Indonesia is holding a democratic party, namely the general elections in 2019. The plurality of parties has represented the many interests of the Indonesian people, who are known to consist of many ethnicities, religions and races. Thus, the interests of the people here are the main thing that must be considered in the 2019 BEM Board Election. The problem that usually arises during campaign momentum is the many hoax (fake) issues circulating that are used to manipulate 2019 campaign news. Spinning this issue is very dangerous, especially for Panca Dharma Vocational School students who are new to political science. Research activities are expected to contribute to opening political insight from an early age among students of Panca Dharma Vocational School